2016
DOI: 10.1186/s12889-016-3598-4
|View full text |Cite
|
Sign up to set email alerts
|

Survival rates and worker compensation expenses in a national cohort of Mexican workers with permanent occupational disability caused by diabetes

Abstract: BackgroundPermanent occupational disability is one of the most severe consequences of diabetes that impedes the performance of usual working activities among economically active individuals. Survival rates and worker compensation expenses have not previously been examined among Mexican workers. We aimed to describe the worker compensation expenses derived from pension payments and also to examine the survival rates and characteristics associated with all-cause mortality, in a cohort of 34,014 Mexican workers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…These results do not consider pension payments for early retirement due to diabetes that would result in a further reduction of the estimated ICER. An analysis of a retrospective cohort of 34,014 Mexican workers with permanent occupational disability caused by T1D and T2D during the years 2000–2013 at IMSS found that the mean age for permanent occupational disability was 51.6 years, and that the expenditure on diabetes-related pensions almost doubled (USD$58.28 to USD$111.62 million) [35]. As such, the results of this analysis may be considered a conservative estimate.…”
Section: Discussionmentioning
confidence: 99%
“…These results do not consider pension payments for early retirement due to diabetes that would result in a further reduction of the estimated ICER. An analysis of a retrospective cohort of 34,014 Mexican workers with permanent occupational disability caused by T1D and T2D during the years 2000–2013 at IMSS found that the mean age for permanent occupational disability was 51.6 years, and that the expenditure on diabetes-related pensions almost doubled (USD$58.28 to USD$111.62 million) [35]. As such, the results of this analysis may be considered a conservative estimate.…”
Section: Discussionmentioning
confidence: 99%
“…The second challenge is the economic burden from indirect costs, since IMSS affiliates are entitled to receive temporary and permanent disability leave and pensions. Between 2000 and 2013, diabetes-related pensions almost doubled, from USD$58.28 million to USD$111.62 million [ 28 ]. From an economic and social perspective, the poor health of T1D patients −particularly chronic complications− have critical consequences such as increased work absence, reduced work productivity, permanent occupational disability, early retirement, shortened life-expectancy and low quality-of-life [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of a retrospective cohort of 34,014 Mexican workers with permanent occupational disability caused by T1D and T2D during the years 2000–2013 at IMSS found that the mean age for permanent occupational disability was 51.6 years. Life expectancy was 7.26 years less, and 55.5 ± 8.0 years (mean, SD) of age at death [ 28 ]. Renal complications are the principal characteristic associated with a significantly elevated all-cause mortality (Hazard Ratio 3.49; 95% CI 3.18–3.83) [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such difference might be explained by the fact that we analyzed the complications that occurred in this entire population, whereas that study evaluated the percentage of complications that were observed among patients applying for a disability pension. 16 However, as pointed out by Arredondo et al, chronic kidney disease, retinopathy, cardiovascular disease, diabetic neuropathy and peripheral vascular disease have a rather high impact on the cost of medical care in Mexico. 17 Microvascular complications were the most frequently recorded (25.4 %), perhaps because they are diagnosed and treated by the family doctor.…”
Section: Discussionmentioning
confidence: 99%